Reply to Stojanowski et al, "Contesting the massacre at Nataruk". - Lahr, M; Rivera, F; Power, R; Mounier, A; Copsey, B; Crivellaro, F; Edung, J; Maillo Fernandez, J; Kiarie, C; Lawrence, J; Leakey, A; Mbua, E; et al. (Nature Publishing Group, 2016)
In the accompanying Comment1, Stojanowski et al. challenge the evidence for inter-group conflict at Nataruk2. They make two arguments — first, that the lesions in three crania are due to soil compression; second, that there is a correlation between body position and age, reflecting different burial traditions. We believe that their interpretation is incorrect on both counts